The Impact of Human Resources Management High Performance on Organizational EntrepreneUrship with the Mediating Role of Organizational Citizenship Behavior - Reza Sepahvand; Mahdieh Moghoyi Nezhad (مطالعات مدیریت بهبود و تحول, 2017)
The aim of this research is to consider the impact of a high performance human resources management on organizational entrepreneurship along with the mediating role of citizenship behavior. The statistical universe of research encompasses 150 employees of education Bureau in the first urban zone of Khorramabad, in which 108 people have been adopted as the sample size through Morgan Table. The sampling method is quite random in this paper.  The data obtained by the questionnaire of organizational citizenship behavior Oregon as well as the created questionnaire of entrepreneurship and high performance human resources were analyzed by structural equation model and Amos18 software. The results have shown that, in 95-percent level of assurance, high performance human resources have a significant positive impact on organizational entrepreneurship. It's been also determined that organizational citizenship behavior plays a meditative role in this impact.